(untitled) (Research, Society and Development, 2022)
Atopic Dermatitis is a very common chronic and inflammatory skin disease that can be identified from its characteristic symptoms, which are skin dryness and erythema, redness. The inflammatory cascade can be triggered by exposure to allergenic proteins even in very low amounts, thus stimulating the high production of Immunoglobulin E, initiating an acute process of inflammation. Currently, treatments are aimed at relieving symptoms with the use of some classes of drugs, among them, topical corticosteroids can be mentioned, such as mometasone furoate cream at 0.1%. There are also some treatments that act at the beginning of the inflammatory process, such as fully human monoclonal antibodies, dupilumab, however, has a high cost. Alternatively, herbal medicine can be used. Chamomile, Matricaria recutita, L., widely used in traditional medicine, contains phytochemicals in its structure that enable pharmacological effects such as anti-inflammatory due to the presence of α-Bisabolol and chamazulene. Topical use of M. recutita, L. extract can serve as a treatment to reduce inflammation and with a low incidence of adverse effects. This work aims to establish a relationship between the use of chamomile and the relief of symptoms presented by the atopic patient, replacing the use of traditional corticosteroids.